Trends regarding percutaneous endoscopic gastrostomy: A nationwide population-based study from 1997 to 2010. Issue 24 (June 2016) - Chang, Wei-Kuo; Lin, Kuen-Tze; Tsai, Chen-Liang; Chung, Chi-Hsiang; Chien, Wu-Chien; Lin, Chun-Shu
Abstract : Abstract: Percutaneous endoscopic gastrostomy (PEG) is widely used in patients requiring long-term tube feeding. Traditional PEG studies usually focused on practical, technical, and ethical issues. There have been little epidemiological studies on PEG utilization and services in Asia. We evaluated the changes in PEG utilization, patient selection, patient characteristics, and medical service in Taiwan from 1997 to 2010. This retrospective study analyzed the data of patients admitted for PEG tube placement according to the International Classification of Diseases, Ninth Revision (procedure code 43.11) extracted from the National Health Insurance database between 1997 and 2010. From 1997 to 2010, the incidence of PEG increased from 0.1 to 3.8/10 5 population and incidence of PEG among aged patients increased from 0.9 to 19.0/10 5 population. Compared 1997–2004 to 2005–2010 periods, the percentage of cerebrovascular diseases decreased and esophageal cancer increased in the later period. PEG was mainly performed in male patients and at medical centers. Medical costs, Charlson Comorbidity Index (CCI) scores, and post-PEG mortality rates were higher in the 2005–2010 period than in the 1997–2004 period. PEG procedures are being increasingly performed in Taiwan, and changes in patient selection were noted. The seriousness of accompanying diseases, medical costs, and post-PEG mortality rates in patients undergoing PEG has increased. The present findings may help in the implementation of PEG, relocation of medical resources, and improvement of PEG-related care.